Influence of smoke suppressant on the smoke inhibition effect and properties of different types of asphalt - Liang, Hehao; Zhao, Pu; Xu, Ruifeng; Liang, Xiayi; Xiao, Xin; Shi, Liwan; Lv, Jin (Frontiers in Materials, 2023)
Abstract: The current understanding of the influence of smoke suppressants on the smoke inhibition effect and working performance of different types of asphalt is limited. In this study, portable gas detector (PGD) tests were used to investigate the influence of the smoke suppressant on different types of asphalt and the smoke purification effect. Subsequently, gas chromatography-mass spectrometry (GC-MS) was used to analyze the influence of the smoke suppressant on the volatile organic compounds (VOCs) in different types of asphalt fume, so as to compare and verify the PGD tests results. Finally, scanning electron microscopy and energy dispersive spectrometry were used to observe and analyze the influence of the smoke suppressant on the microstructure and element composition of different types of asphalt. The results show that the smoke suppressant can purify various harmful gases volatilized from different types of asphalt, but the effect and the optimal dosage of smoke suppressant are slightly different. The purification rate of the smoke suppressant for SO2 or H2S in the fumes of various asphalts can reach > 70% and the NO and VOC purification rates can reach > 40%. The influence of the smoke suppressant on the VOC purification rate of different asphalts detected through the GC-MS and PGD tests is similar. The smoke suppressant has little effect on the asphalt surface microstructure and on the changes in the element content in asphalt, indicating that it has no effect on the main properties of the asphalt itself. This study is helpful to further understand the relationship between smoke suppressants and the smoke inhibition effect and the working performance of different types of asphalt. Additionally, it provides basis and guidance for the development of low-smoke asphalt with a better emission reduction effect, which has a certain guiding and application significance.